Exergy of solar radiation. (5th April 2005) - Kabelac, Stephan
Solar radiation reaching the ground is accompanied with radiation entropy. When the entropy production rate within any solar energy conversion device is to be calculated, the incoming radiation entropy flux has to be known. In this contribution, first it is shown how the radiation entropy flux arriving on earth is to be calculated. Secondly, the interaction between the incoming radiation and the receiver surface is identified as one entropy production source. An approach for a reversible radiation conversion device is proposed. Maximum conversion efficiencies for non-concentrating solar energy converters are found to be between 50–77% of the incoming radiation energy, depending on atmospheric conditions.